Career pathways and professional skills of postgraduate students from a dental research-intensive programme - Kumari Amrita; Wu David T.; Motiani Kumail K.; Wu Kevin Y.; Palumbo Maria; Tran Simon D. (Wiley-Blackwell, 2022)
With current global trends in postgraduate education, graduate programmes must make evidence-based improvements to offer the best programme that aligns with student needs and prepare them for their future career prospects. The aim of this cross-sectional study was to investigate the postgraduation career pathways of MSc and PhD students who graduated within the past 15 years from the McGill University Postgraduate Dental Research Program.
An online questionnaire, composed of 10 closed-ended format items, was used that covered domains such as student profile, career profile, postgraduate skill development, job search experience and satisfaction. Descriptive statistics and interpretative qualitative analysis were used to evaluate student feedback.
Sixty-six students responded to the online survey, out of which sixty-two students completed the survey (61% participation rate). The majority of the graduate students, 67% (n = 44), obtained MSc degree in Dental Sciences. Overall, our results showed that most graduates started careers in academia in their original field of study and were satisfied with their income. Most graduates reported "critical and creative thinking" to be the strongest acquired skills during their postgraduate training and identified fierce competition for their position of interest as the main challenge after graduation.
Our results showed that graduates in dental research appeared to be overall satisfied with their careers after postgraduate research training, both in terms of scope of practice and income. However, strong competition in obtaining the position of their interest seemed to be the main obstacle after graduation.